Modernizing HRM for Global Small and Medium-Sized Businesses - Zahera Mega Utama; Abdul Wahab Samaad (Journal of Center for Energy Policy and Human Resources Capacity Development, 2025)
Abstract: This study seeks to elucidate the function of human resources management (HRM) within Small and Medium Enterprises (SMEs). In an age of globalization and internationalization, SMEs participate in cross-border commerce and worldwide collaborations. Efficient human resource management is crucial for fostering the development and prosperity of these enterprises. Human Resource Management activities include recruitment, training, remuneration, legal compliance, and occupational health. Effectively managing these components facilitates the attainment of the company's strategic objectives. The incorporation of millennials into the workforce necessitates that HRM handle cultural concerns, workplace safety, integration, and work-life balance. Innovations and digitization have revolutionized corporate operations, necessitating that HRM comprehends the significance of technology and guarantees its efficient implementation. The present era signifies a pivotal moment for the comeback of Human Resource Management. Adapting to and comprehending dynamic changes in the workplace are essential for addressing global and multicultural concerns. By understanding and addressing these factors, SMEs may guarantee that their HRM positively influences sustained organizational success.